Upper‐limb acute superficial lymphatic thrombosis: A case report. Issue 10 (3rd October 2022) - Hamdan, Rémy; Briche, Nicolas; Gasmi, Vanessa; Abejiou, Ilham; Lafon, Ingrid; Djerroudi, Lounes
Abstract: Upper‐limb acute superficial lymphatic is a rare phenomenon that has received little attention in the medical literature to date, yet it mimics superficial venous thrombosis and may also complicate a skin punch biopsy. Abstract : This report highlights the clinical implications of in vitro‐demonstrated lymphatic vessels' ability to thrombose. The differential diagnosis list for superficial venous thrombosis is enlarged. Like veins, hypercoagulability, endothelial changes, and stasis may result in acute lymphatic thrombosis. Additionally, here, we report for the first time an unknown acute skin biopsy complication.